Iodine-to-calcium ratios in deep-sea scleractinian and bamboo corals - Sun, Yun-Ju; Robinson, Laura F.; Parkinson, Ian J.; Stewart, Joseph A.; Lu, Wanyi; Hardisty, Dalton S.; Liu, Qian; Kershaw, James; LaVigne, Michèle; Horner, Tristan J. (Frontiers in Marine Science, 2023)
The distribution of dissolved iodine in seawater is sensitive to multiple biogeochemical cycles, including those of nitrogen and oxygen. The iodine-to-calcium ratio (I/Ca) of marine carbonates, such as bulk carbonate or foraminifera, has emerged as a potential proxy for changes in past seawater oxygenation. However, the utility of the I/Ca proxy in deep-sea corals, natural archives of seawater chemistry with wide spatial coverage and radiometric dating potential, remains unexplored. Here, we present the first I/Ca data obtained from modern deep-sea corals, specifically scleractinian and bamboo corals, collected from the Atlantic, Eastern Pacific, and Southern Oceans, encompassing a wide range of seawater oxygen concentrations (10–280 μmol/kg). In contrast to thermodynamic predictions, we observe higher I/Ca ratios in aragonitic corals (scleractinian) compared to calcitic corals (bamboo). This observation suggests a strong biological control during iodate incorporation into deep-sea coral skeletons. For the majority of scleractinian corals, I/Ca exhibits a covariation with local seawater iodate concentrations, which is closely related to seawater oxygen content. Scleractinian corals also exhibit notably lower I/Ca below a seawater oxygen threshold of approximately 160 μmol/kg. In contrast, no significant differences in I/Ca are found among bamboo corals across the range of oxygen concentrations encountered (15–240 μmol/kg). In the North Atlantic, several hydrographic factors, such as temperature and/or salinity, may additionally affect coral I/Ca. Our results highlight the potential of I/Ca ratios in deep-sea scleractinian corals to serve as an indicator of past seawater iodate concentrations, providing valuable insights into historical seawater oxygen levels.